From the notebooks of Melanin Sun - Woodson, Jacqueline (New York : Blue Sky Press, 1995)
Almost-fourteen-year-old Melanin Sun's comfortable, quiet life is shattered when his mother reveals she has fallen in love with a woman.
Keywords: Mothers and sons -- Fiction; Lesbians -- Fiction; African Americans -- Fiction; Brooklyn (New York, N.Y.) -- Fiction